2015
DOI: 10.1002/jso.23923
|View full text |Cite
|
Sign up to set email alerts
|

Absence or low IGF‐1R‐expression in esophageal adenocarcinoma is associated with tumor invasiveness and radicality of surgical resection

Abstract: Absence or low expression of IGF-1R was associated with high grade- and advanced tumors and less radical resections. IGF-1R might be a tumor marker in Barrett's esophagus since a change in expression patterns was found in the course from normal esophageal tissue to adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This finding is furthermore reflected in the lower levels of these IGF pathway proteins and their mRNAs in association with shorter 10-year disease-free survival and overall rates. A decrease in both IGF1R protein and gene expression levels has been described before in esophageal adenocarcinoma, colorectal and breast cancer (Schnarr et al 2000, Allison et al 2007, Kuklinski et al 2011, De Bruijn et al 2015 and might reflect a dedifferentiation process. Indeed, two recent genomic studies have identified distinctive m(i) RNA expression profiles, separating PanNET with liver metastases (metastasis like primary tumor subtype) from well-differentiated PanNETs (well-differentiated islet/insulinoma tumor subtype), further underscoring dedifferentiation to be reflected in gene expression signatures (Sadanandam et al 2015, Scarpa et al 2017.…”
Section: Discussionsupporting
confidence: 54%
“…This finding is furthermore reflected in the lower levels of these IGF pathway proteins and their mRNAs in association with shorter 10-year disease-free survival and overall rates. A decrease in both IGF1R protein and gene expression levels has been described before in esophageal adenocarcinoma, colorectal and breast cancer (Schnarr et al 2000, Allison et al 2007, Kuklinski et al 2011, De Bruijn et al 2015 and might reflect a dedifferentiation process. Indeed, two recent genomic studies have identified distinctive m(i) RNA expression profiles, separating PanNET with liver metastases (metastasis like primary tumor subtype) from well-differentiated PanNETs (well-differentiated islet/insulinoma tumor subtype), further underscoring dedifferentiation to be reflected in gene expression signatures (Sadanandam et al 2015, Scarpa et al 2017.…”
Section: Discussionsupporting
confidence: 54%
“…For the construction of a tissue microarray (TMA), formalin‐fixed paraffin‐embedded tissue from the resection specimens was retrieved from the archives at the Departments of Pathology of the participating institutions. For each tumour, three to six cores from multiple representative areas of OAC, as identified by a pathologist on haematoxylin and eosin‐stained slides, were taken from the original paraffin blocks, including the central part and invasive front of the tumour.…”
Section: Methodsmentioning
confidence: 99%
“…Reports on the association between tissue expression of IGF-1R and survival in OAC have been mixed. De Bruijn et al [29] found that absence or low expression of IGF-1R was associated with high grade and advanced tumours, less radical resections and decreased OS but not decreased DFS on univariate analysis. Doyle et al [120] found no association between IGF-1R expression in tissue samples and obesity status, tumour stage, nodal status, or survival, however, they noted that in both OAC and SCC sections, increased levels of IGF-1R expression were observed in tumour cells within islets and at the invasive edge compared with tumour-associated stromal cells, this coincided with increased levels of CD68+ macrophages which are a known source of IGF-1 secretion and likely aid the growth of IGF-1R+ positive tumours.…”
Section: Igf-1rmentioning
confidence: 99%